Modification of Epoxidized Soybean Oil for the Preparation of Amorphous, Nonretrogradable, and Hydrophobic Starch Films - Sara Dalle Vacche; Leandro Hernan Esposito; Daniele Bugnotti; Emanuela Callone; Sara Fernanda Orsini; Massimiliano D’Arienzo; Laura Cipolla; Simona Petroni; Alessandra Vitale; Roberta Bongiovanni; Sandra Dirè (Polysaccharides, 2025)
Starch was plasticized with epoxidized soybean oil (ESO) modified by reaction with cinnamic acid (CA), and films were prepared using solvent casting from water/ethanol solutions. They exhibited good hydrophobicity, reduced water sensitivity, and showed the same transparency as glycerol-plasticized counterparts, but with less flexibility. Interestingly, modified ESO enhanced gelatinization and hindered retrogradation of the biopolymer. ESO was reacted with CA without the use of catalysts to obtain a β-hydroxyester; in order to optimize the synthesis process, different reaction conditions were explored, varying the stoichiometry and the heating cycles. Products were fully characterized by Fourier transform infrared (FTIR) spectroscopy, 1H and 13C nuclear magnetic resonance (NMR), and the different reactions following the opening of the oxirane ring were discussed. The properties of the novel starch-based films prepared with modified ESO highlight their use in food packaging, disposable devices, and agricultural mulching films.